Conversion of motorcycles to electric vehicles towards sustainable mobility - A.D. Santoso; H. Daulay; A. Priyanti; M. Silalahi; U.K. Yaumidin; N. Irawati; H. Sumartono; P. Astuti; A.R. Farandy; A. Parikesit; M.F. Manti; E. Indriasari; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Developing Southeast Asian countries, including Indonesia, have significant hurdles in addressing the increasing usage of motorized vehicles and their detrimental impact on air quality, traffic, energy security, liability, and greenhouse gas emissions. is to assess the viability of transforming traditional internal combustion engine motorcycles into electric vehicles powered by batteries in Indonesia. The analysis will concentrate on the positive environmental outcomes, including decreased greenhouse gas emissions and energy usage, in addition to examining the economic and social consequences of this transition. The absence of exhaust emissions could create the impression that converting to battery-powered electric vehicles will consistently yield favorable environmental outcomes, such as reducing greenhouse gas emissions and energy consumption. Meanwhile, the economic and social impacts associated with electric vehicle conversion programs are also taken into account savings during post-conversion.METHODS: Primary data was acquired through the distribution of questionnaires, conducting in-depth interviews with workshop managers, and obtaining scientific evaluations from participating experts. The Rapfish multidimensional scaling application was used to handle and evaluate the data. The analysis of the data involved the examination of five dimensions, namely social, economic, ecological, technological, and institutional, with each dimension comprising 37 variables.FINDINGS: The sustainability index, which stands at 70.39 percent, indicating a fair level of sustainability, implies that there is significant development potential in the conversion process of internal combustion engine motorbikes to battery electric vehicles by strategically focusing on key leverage factors across various dimensions. The institutional dimension registers the lowest value at 48.92 percent, whereas the environmental, technological, social, and economic dimensions’ exhibit values of 85.25 percent, 79.13 percent, 76.29 percent, and 62.37 percent, respectively. Achieving sustainability requires focused enhancements in various key areas: setting up waste conversion facilities in the environmental aspect, educating employees on environmental conservation and boosting business incentives in the social aspect, ensuring a stable supply of raw materials and maximizing market penetration in the economic aspect, and improving experience management and skill acquisition in the technological aspect. Additionally, the presence of funding, the involvement of marketing intermediaries, and the backing for initiatives aimed at converting vehicles to electric power within the institutional framework are key aspects that demand concentrated efforts.CONCLUSION: The multidimensional assessment indicates that Indonesia's electric vehicle conversion program is progressing effectively, achieving an average sustainability index of 70.39 percent, categorized as fair. The results indicate that the initiative has effectively created a resilient, sustainable conversion framework that can be tailored to various environments and scenarios. To further enhance sustainability within these conversion initiatives, it is imperative to prioritize institutional dimensions, particularly financial and marketing support, as well as the critical role of the electric vehicle conversion itself. This model provides significant perspectives for policymakers and government entities when developing and executing forthcoming policies and initiatives.